Analisis Kesiapan Calon Guru Sekolah Dasar Dalam Menghadapi Era Revolusi Industri 4.0 - Gustiana Tri W; Cyndi Salma; Ariana Rizky (Program Studi PGSD Kampus UPI di Serang, 2021)
This research aims to analyze the readiness of prospective elementary school teachers who are students of the Elementary School Teacher Education (PGSD) study program of the State University of Education in facing the era of the industrial revolution in terms of educational competence, competence for technological commercialization, competence in globalization, competence in the future strategies, and counselor competence. The research used a qualitative approach with a case study model. The results showed that the ability of prospective teachers in terms of these five aspects showed good results, namely from the aspect of educational competence. The results are quite good for the aspects of counselor competence. And the results are less for competence for technological commercialization, competence in globalization, and competence in future strategies.